Persepsi Guru Madrasah Ibtidaiyah Terhadap Pembelajaran Daring Selama Program Belajar Dari Rumah (BDR) di Masa Pandemi COVID-19 - Arifin, Ahmad Syamsul; Sukati, Sukati (Literasi: Jurnal Ilmu Pendidikan, 2020)
The Covid-19 Pandemic has caused a number of educational institutions in Indonesia to be temporarily closed. Learning activities in a number of areas are carried out online and eliminate face-to-face learning. The implementation of online learning in Indonesia, including in Bantul DIY district, is not an easy matter because it is a new way of adapting to the new Indonesian education system. This study aims to explore teachers' perceptions of online learning that have been held during the Covid-19 pandemic.The research method used in this research is descriptive quantitative research which aims to describe the teacher's perceptions of the effectiveness of online learning during the Covid-19 pandemic. Respondents in this study were 46 teachers. The data collection technique used was a questionnaire that was submitted to the respondents online (social media and electronic mail).Based on the results of the study, it was found that all Islamic elementary school (Madrasah Ibtidaiyah) teachers in Bantul had implemented online learning. Even so, most of the respondents stated that online learning was not yet effective (69.60%). This is influenced by limited infrastructure, the readiness of parents to provide assistance to children while learning from home, and some teachers have not been able to respond and adapt to this online learning properly and effectively.Keywords: teacher perceptions, online learning, pandemic covid-19